High‐Speed Recording of Cardiomyocyte Calcium and Contraction: Ultra‐low light calcium signaling measured at high speeds. Issue 4 (2nd November 2016) - Louch, William E.; Frisk, Michael; Eggart, Benjamin
Abstract: Investigating the dynamic balances of ion fluxes, electrical potentials, and pH is crucial to understanding fundamental functions within living cells. Imaging is a common measurement technique used to study these vital parameters. The simultaneous measurement of fluorescent signals and cell shape contraction however, remains challenging due to different wavelengths or alignment of light paths. This article describes the advantages of using the W‐View Gemini image splitting device to observe brightfield and fluorescence signals simultaneously, at a very high acquisition rate.